Analisis Sistem Pengendalian Internal Dalam Pengelolaan Risiko Kehilangan Air Non Fisik Pada PDAM Tirtawening - Silvana Septiany Rahmat; Etti Ernita Sembiring (Indonesian Accounting Literacy Journal, 2021)
This research aims to determine the internal control system in managing water loss risk at PDAM Tirtawening. The research method used descriptive qualitative with interview and documentation data collection techniques. The data analysis tool that researcher use was COSO and Control Matrix. This research also used qualitative data types and primary data sources. The result showed that The Internal Control System at PDAM Tirtawening was quite effective and need to be improved again to deal with the risks that may arise such as non physical water loss. The various of non physical water loss was illegal connection and water theft, and administrative errors. Illegal connection and water theft were consist of illegal consumption and illegal connection. While administrative errors were consist of reader meter administrative errors, account creation errors, customer database errors, and data collection and transfer errors.